2021
DOI: 10.1159/000510346
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Femtosecond Laser-Assisted Cataract Surgery for Cataracts due to Atopic Dermatitis

Abstract: We retrospectively evaluated the efficacy and safety of femtosecond laser-assisted cataract surgery (FLACS) for cataracts due to atopic dermatitis, which are often complicated by intumescent white cataract (IWC) and subcapsular fibrosis. Thirty-seven eyes of 30 cataract patients diagnosed with atopic dermatitis were included in the study. Nine eyes had IWC, and 13 eyes had anterior subcapsular fibrosis characteristic of atopic cataracts. Free-floating capsulotomy was achieved in 32 eyes (86%). Three eyes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A case study of 30 eyes found that FLACS was an effective method for avoiding radial anterior capsular tear, vitreous loss, and IOL dislocation in cataracts caused by atopic dermatitis, including intumescent white cataracts and eyes with anterior subcapsular fibrosis. The study noted that incomplete capsulotomies occurred at a significantly higher rate for intumescent cataracts where leakage of lens material was observed [36]. Similarly, in a study of 58 white cataracts treated with FLACS, Chee et al [37] found that no incidences of Argentinian flag sign occurred but that incomplete capsulotomies were significantly associated with increased lens thickness and Morganian cataracts.…”
Section: Femtosecond Laser Capsulotomymentioning
confidence: 91%
“…A case study of 30 eyes found that FLACS was an effective method for avoiding radial anterior capsular tear, vitreous loss, and IOL dislocation in cataracts caused by atopic dermatitis, including intumescent white cataracts and eyes with anterior subcapsular fibrosis. The study noted that incomplete capsulotomies occurred at a significantly higher rate for intumescent cataracts where leakage of lens material was observed [36]. Similarly, in a study of 58 white cataracts treated with FLACS, Chee et al [37] found that no incidences of Argentinian flag sign occurred but that incomplete capsulotomies were significantly associated with increased lens thickness and Morganian cataracts.…”
Section: Femtosecond Laser Capsulotomymentioning
confidence: 91%
“…Yamazaki et al. 41 found that patients with atopic cataract can also get FLACS safely despite anterior subcapsular fibrosis and/or intumescent white cataract (IWC). Recent studies 42 , 43 , 44 on cataract patients with Fuchs endothelial corneal dystrophy indicated that FLACS may perform better than conventional phacoemulsification in the reduction of corneal endothelial cell loss and CCT changes.…”
Section: Femtosecond Laser-assisted Cataract Surgerymentioning
confidence: 99%